Training Employers to Implement Health Promotion Programs: Results From the CDC Work@Health(®) Program - Cluff, Laurie A. (Am J Health Promot, 2017)
PURPOSE: Centers for Disease Control and Prevention (CDC) initiated the Work@Health Program to teach employers how to improve worker health using evidence-based strategies. Program goals included (1) determining the best way(s) to deliver employer training, (2) increasing employers’ knowledge of workplace health promotion (WHP), and (3) increasing the number of evidence-based WHP interventions at employers’ worksites. This study is one of the few to examine the effectiveness of a program designed to train employers how to implement WHP programs. DESIGN: Pre- and posttest design. SETTING: Training via 1 of 3 formats hands-on, online, or blended. PARTICIPANTS: Two hundred six individual participants from 173 employers of all sizes. INTERVENTION: Eight-module training curriculum to guide participants through building an evidence-based WHP program, followed by 6 to 10 months of technical assistance. MEASURES: The CDC Worksite Health ScoreCard and knowledge, attitudes, and behavior survey. ANALYSIS: Descriptive statistics, paired t tests, and mixed linear models. RESULTS: Participants’ posttraining mean knowledge scores were significantly greater than the pretraining scores (61.1 vs 53.2, P < .001). A year after training, employers had significantly increased the number of evidence-based interventions in place (47.7 vs 35.5, P < .001). Employers’ improvements did not significantly differ among the 3 training delivery formats. CONCLUSION: The Work@Health Program provided employers with knowledge to implement WHP interventions. The training and technical assistance provided structure, practical guidance, and tools to assess needs and select, implement, and evaluate interventions.